2016
DOI: 10.1007/s00784-016-2028-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of a glass ionomer restorative system: a 6-year evaluation

Abstract: The clinical effectiveness of Equia and Gradia Direct Posterior was acceptable in Cl1 and Cl2 cavities subsequent to 6-year evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 27 publications
5
49
0
11
Order By: Relevance
“…The results of the present study reported no significant differences in shade matching, postoperative sensitivity, material handling, secondary caries, and marginal staining between GC (EQUIA) and the resin composite (Amelogen Plus, Ultradent) used for class I cavities in permanent teeth; this is in accordance with a recent published study by Gurgan et al 17 that evaluated the clinical performance over 6 years of GIC systems, concluding an acceptable behavior of EQUIA over time. Another clinical report showed that the EQUIA system, based on a high-viscosity resin-coated GIC cement, seems to be a reliable choice for long-term dental restorations, even in load-bearing teeth surfaces.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study reported no significant differences in shade matching, postoperative sensitivity, material handling, secondary caries, and marginal staining between GC (EQUIA) and the resin composite (Amelogen Plus, Ultradent) used for class I cavities in permanent teeth; this is in accordance with a recent published study by Gurgan et al 17 that evaluated the clinical performance over 6 years of GIC systems, concluding an acceptable behavior of EQUIA over time. Another clinical report showed that the EQUIA system, based on a high-viscosity resin-coated GIC cement, seems to be a reliable choice for long-term dental restorations, even in load-bearing teeth surfaces.…”
Section: Discussionsupporting
confidence: 92%
“…6,7,[14][15][16][17][18][19][20] Knowledge of the mechanical properties of a material, with regard to its surface protection using a self-adhesive coating agent, can elucidate its behavior and, therefore, determine its clinical uses and performance. Hence, in the present laboratory study the aim was to compare flexural strength and hardness of seven aesthetic restorative materials, asses the effect of storage in distilled deionized water (DDW) for up to six months, and determine the effect of resin surface coating on the mechanical properties of the materials.…”
Section: Accepted Articlementioning
confidence: 99%
“…14 The use of glass ionomer cements has increased since their introduction in the 1970s, because they have many characteristics of an ideal restorative material, such as similarity to tooth color, uniting with tooth structure, radiopacity, releasing fluoride over time, inhibiting demineralization, tissue compatibility, and contributing remineralization of adjacent dentin. [15][16][17][18] Furthermore, they are the most used filling material for minimally invasive restorations. 19 The longevity of composite resin restorations is directly related to some factors, such as marginal seal and good adaptation to the cavity walls of the preparation.…”
Section: 5005/jp-journals-10024-2061mentioning
confidence: 99%